Development of a recombinant vaccine against human onchocerciasis. (2nd November 2021) - Abraham, David; Graham-Brown, John; Carter, Darrick; Gray, Sean A.; Hess, Jessica A.; Makepeace, Benjamin L.; Lustigman, Sara
ABSTRACT: Introduction: Human onchocerciasis caused by the filarial nematode parasite Onchocerca volvulus remains a major cause of debilitating disease infecting millions primarily in Sub-Saharan Africa. The development of a prophylactic vaccine, along with mass drug administration, would facilitate meeting the goal of onchocerciasis elimination by 2030. Areas covered: Models used to study immunity to Onchocerca include natural infection of cattle with Onchocerca ochengi and O. volvulus infective third-stage larvae implanted within diffusion chambers in mice. A vaccine, comprised of two adjuvanted recombinant antigens, induced protective immunity in genetically diverse mice suggesting that it will function similarly in diverse human populations. These antigens were recognized by immune humans and also induced protective immunity against Brugia malayi . We describe the development of a fusion protein composed of the two vaccine antigens with the plan to test the vaccine in cows and non-human primates as a prelude to the initiation of phase 1 clinical trials. Expert opinion: The adjuvanted O. volvulus vaccine composed of two antigens Ov -103 and Ov -RAL-2 was shown to be consistently effective at inducing protective immunity using multiple immune mechanisms. The vaccine is ready for further evaluation in other animal models before moving to clinical trials in humans.